Experimental Investigation of shading facade-integrated solar absorber system under hot tropical climate - Ng, Khai Mun; Adam, Nor Mariah; Ab Kadir, Mohd Zainal Abidin (Elsevier, 2019)
In this paper, a shading façade-integrated solar absorber system has been assessed outdoors under the hot tropical climate. The system was developed, and its performance was tested for 79 days under a standard system operating condition. The outdoor field test has demonstrated that the system was principally dependent on the available global irradiance, and its performance was impaired by the high occurrence of afternoon rain. On average, the system was capable to achieve a daily efficiency of 50.5%, maximum daily water temperature attained at 48.9 °C, and solar water heating rate of 2.9 °C/h. Findings showed that the system could perform most frequently at a daily efficiency ranging from 45% to 60%, and the maximum daily water temperature attained from 45 °C to 57 °C during the test period. Empirical results indicate that there exist several linear regressions between the variables that show acceptable correlations. An additional experiment was carried out to assess the heat distribution mapping of the experimental model.